Unsaturated characteristics of ballast fouling materials and fouled ballast - Sherwood, Robert R. (Kansas State University, 2020)
Fouling reduces ballast drainage and strength. Without detection and remediation, track geometry degrades and risk of train derailment increases; therefore, fouling must be managed. There is limited research about the characteristics of fouled ballast needed to improve detection and remediation methods. This research specifically focused on the water holding capacity of fouled ballast. Soil water characteristic curves (SWCCs) were measured on 14 ballast fouling specimens using a 66.0 mm tall 61.8 mm diameter flow cell and using the transient water release and imbibition method (TRIM). SWCCs were also calculated for 21 fouled ballast specimens using the Bouwer-Rice Large Particle Correction Procedure. Lastly, SWCCs were measured on two fouled ballast specimens (with aggregate sizes up 42.5 mm, nominal diameter) using a custom 178 mm tall 255 mm diameter flow cell and the TRIM. SWCCs of the ballast fouling specimens show that the presence of coal fines greatly influences water retention. Calculated results for the fouled ballast specimens show that the type of fouling material and the quantity of fouling material in a fouled ballast layer dominate several engineering properties of the layer (e.g., hydraulic conductivity and pore water content). The results in the custom larger cell validate the novel experimental testing plan with aggregates to support measuring SWCCs of fouled ballast. This research is the first step in characterizing these materials to support in situ identification of fouled ballast using ground penetrating radar (GPR). Future work correlating dielectric measurements to SWCC measurements of fouled ballast specimens is hypothesized to help uncouple water content and fouling conditions in GPR measurements.
Keywords: Fouled ballast; Ballast fouling material; Soil water characteristic curve; Unsaturated ballast; Ballast